Studi Pemikiran Pendidikan Islam Tradisional Dan Modern - Moh Hasibuddin; Mahfida Inayati; Mohammad Hasan (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
Traditional Islamic education thinking is one of the Islamic understandings that is widely adopted by the Indonesian population and this is very popular. This modern Islamic educational thinking is not only enjoying an increasingly advanced era but still relies on the Qur'an and Sunnah so that Muslims remain on the source of their teachings that are never worn down by the times. With the traditional concepts of tarbiyah, ta'lim and ta'dib while the modern concept relies on science and technology. But it does not diminish in the slightest about religious education, as the golden age used to be. The search for a new paradigm in Islamic education starts from the concept of man according to Islam, the Islamic view of science and technology, and after that the concept or system of Islamic education as a whole is formulated.